2001
DOI: 10.1143/jjap.40.l1116
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Multistep Laser Etching of Transparent Amorphous Organic Film

Abstract: Calculational results are presented from an extensive study of the hydro-burn response of bare DT shells, inert shells, and DT-filled micro-balloons to ramp-like, Gaussian, and square laser pulses. Scaling laws are determined for the best pulse energy and time scale for shells, as functions of their mass, aspect ratio and initial density. The advantages of DT ice over DT gas in the microballoons are demonstrated. An equivalence rule is established between linear ramp pulses and Gaussians, and a connection is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Such interference has been observed to modify the laser breakdown threshold for damage in single layer dielectric [3,4] and multilayered dielectric films [5] by enhancing the internal laser light intensity. Similar interference effects were also inferred by Hosokawa and co-authors [6,7] to underlie a periodic ablation rate in Cu-phthalocyanine amorphous thin films. However, laser ablative structuring internally in such transparent films has not been reported on such interference patterns until recently.…”
Section: Introductionsupporting
confidence: 82%
“…Such interference has been observed to modify the laser breakdown threshold for damage in single layer dielectric [3,4] and multilayered dielectric films [5] by enhancing the internal laser light intensity. Similar interference effects were also inferred by Hosokawa and co-authors [6,7] to underlie a periodic ablation rate in Cu-phthalocyanine amorphous thin films. However, laser ablative structuring internally in such transparent films has not been reported on such interference patterns until recently.…”
Section: Introductionsupporting
confidence: 82%
“…17 In the case of thin transparent films, multisurface Fresnel reflections of laser light can also interfere and create a standing wave interference pattern with fringe maxima spaced by l/2n film inside the film, where n film is the refractive index of the film. 18 Such fringe effects were inferred by Hosokawa and co-workers 19,20 to explain multistep etching of Cu-phthalocyanine amorphous films driven by dissociation of weak intermolecular bonds. However, such fine patterning is not available for the majority of transparent materials such as dielectrics, requiring more aggressive laser interactions than photochemical response or intermolecular bond dissociation.…”
Section: Introductionmentioning
confidence: 92%
“…Ablated fragments formed by femtosecond laser irradiation have been investigated using an atomic force microscope in air, and it was confirmed that fragment sizes ranged from a few ten nanometer to a few micrometer. 10) As the fluence at which the subsequent crystal growth took place was similar to the ablation threshold, it is reasonable to consider that the subsequent crystal growth was initiated by the etching due to the femtosecond laser ablation, 11,12) leading to the ejection of urea crystal fragments. Because the surrounding urea solution is supersaturated, the ejected fragments will act as new seed crystals and grow in the solution.…”
mentioning
confidence: 99%